Diagnostic Ultrasound Physics and Equipment - Hoskins, P. R. (Peter R.); Martin, Kevin, 1948-; Thrush, Abigail (Milton : CRC Press LLC, 2019)
This popular text provides a comprehensive, yet accessible, introduction to the physics and technology of medical ultrasound, with high quality ultrasound images and diagrams throughout. Covering all aspects of the field at a level that meetings the requirements of accredited sonography courses, it is ideal for both trainee and qualified healthcare professionals practising ultrasound in a clinical setting. Building on the content of previous editions, this third edition provides the latest guidance relating to ultrasound technology, quality assurance and safety and discusses the latest techniques.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Diagnostic ultrasonic imaging; MEDICAL / General; MEDICAL / Radiology & Nuclear Medicine; SCIENCE / Physics